Utility of a simplified ultrasound assessment to assess interstitial pulmonary fibrosis in connective tissue disorders - preliminary results - Gutierrez, Marwin (BioMed Central, 2011)
INTRODUCTION: Interstitial pulmonary fibrosis (IPF) is a frequent manifestation in patients with connective tissue disorders (CTD). Recently the ultrasound (US) criterion validity for its assessment has been proposed; however, the US scoring systems adopted include the study of several lung intercostal spaces (LIS), which could be time-consuming in daily clinical practice. The aim of this study was to investigate the utility of a simplified US B-lines scoring system compared with both the US comprehensive assessment and the high-resolution computed tomography (HRCT) findings of IPF in CTD patients. METHODS: Thirty-six patients with a diagnosis of CTD were enrolled. Each patient underwent chest HRCT and lung US by an experienced radiologist and rheumatologist, respectively. Both comprehensive and simplified US B-lines assessments were scanned. The comprehensive US assessment was performed at 50 LIS level, whereas the simplified US assessment included bilaterally 14 LIS; for the anterior chest: the second LIS along the para-sternal lines, the fourth LIS along the mid-clavear, anterior axillary and mid-axillary lines; for the posterior chest: the eighth LIS along the paravertebral, sub-scapular and posterior axillary lines. For criterion validity, HRCT was considered the gold standard. Feasibility, inter and intra-observer reliability was also investigated. RESULTS: A highly significant correlation between comprehensive and simplified US assessment was found (P = 0.0001). A significant correlation was also found between the simplified US assessment and HRCT findings (P = 0.0006). Kappa values for the inter-observer simplified US assessment were in a range from 0.769 to 0.885, whereas the concordance correlation coefficient values for the intra-observer were from 0.856 to 0.955. There was a relevant difference in time spent on comprehensive (mean 23.3 ± SD 4.5 minutes) with respect to the simplified US assessment (mean 8.6 ± SD 1.4) (P < 0.00001). CONCLUSIONS: Our results provide a new working hypothesis in favor of the utility of a simplified US B-lines assessment as an adjunct method to assess IPF in patients with CTD.